2022
DOI: 10.3390/su14127484
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Coordination and Spatiotemporal Evolution between Carbon Emissions, Industrial Structure, and Regional Innovation of Counties in Shandong Province

Abstract: Industrial structure and regional innovation have a significant impact on emissions. This study explores, from the multivariate coupling and spatial perspectives, the degree of coupling coordination between three factors: industrial structure, carbon emissions, and regional innovation of 97 counties in Shandong Province, China from 2000 to 2017. On the basis of global spatial autocorrelation and cold and hot spots, this article analyzes the spatial characteristics and aggregation effects of coupled and coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In low-innovation technology fields, emissions tended to be higher, but with more advancement and patents, emissions eventually started to decline. Wang et al [45] used data from 97 counties in China from 2000-2017 to test the effects of industrial structure and innovations on CO 2 emissions. An analysis showed that there were regional differences in these variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In low-innovation technology fields, emissions tended to be higher, but with more advancement and patents, emissions eventually started to decline. Wang et al [45] used data from 97 counties in China from 2000-2017 to test the effects of industrial structure and innovations on CO 2 emissions. An analysis showed that there were regional differences in these variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of estimating carbon emissions from energy consumption, the “China Energy Statistical Yearbook” only counts energy consumption data at the provincial level, and it is difficult to obtain energy consumption data at the county level. Although the CEAD has published carbon emissions from energy consumption at the county level in China, the data are only available up to 2017, and the publication of the carbon emissions data is not timely [ 79 ]. To ensure the timeliness and uniformity of the research data, we estimated the carbon emissions at the county level from 2000 to 2020 based on the carbon emissions from energy consumption and night-time light data in Shandong Province.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing a coupling coordination model of SEE [58,59]. Then measure the degree of interaction between SEE and each other.…”
Section: Coupling Coordination Modelmentioning
confidence: 99%